2016
DOI: 10.1016/j.ccl.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Automated Quantitative Nuclear Cardiology Methods

Abstract: Quantitative analysis of SPECT and PET has become a major part of nuclear cardiology practice. Current software tools can automatically segment the left ventricle, quantify function, establish myocardial perfusion maps and estimate global and local measures of stress/rest perfusion – all with minimal user input. State-of-the-art automated techniques have been shown to offer high diagnostic accuracy for detecting coronary artery disease, as well as predict prognostic outcomes. This chapter briefly reviews these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 54 publications
(61 reference statements)
0
3
0
1
Order By: Relevance
“…The SRS indicates the degree of ischemia and infarct ( 32 ) and is often correlated with fixed ischemia. Previously, cardiologists and nuclear physicians mainly relied on SRS, TPD, and gated parameters to analyze the severity of myocardial infarction, prognostic information, and treatment decisions ( 9 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…The SRS indicates the degree of ischemia and infarct ( 32 ) and is often correlated with fixed ischemia. Previously, cardiologists and nuclear physicians mainly relied on SRS, TPD, and gated parameters to analyze the severity of myocardial infarction, prognostic information, and treatment decisions ( 9 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…The adjunctive role of automated analyses in nuclear cardiology practice is at least partially associated with a main drawback of software packages, which cannot explicitly differentiate between real perfusion abnormalities and artefacts [ 8 ]. In addition, although the performance of the software packages has been demonstrated to be similar, certain differences in the magnitudes of the derived values have been reported [ 18 ]. In particular, comparing the diagnostic performance of three software packages (ECTb, QPS, and 4DMSPECT), Wolak et al reported differences in myocardial perfusion quantification, while Knollmann et al found differences in measurements (derived from QPS and 4DMSPECT), using either manufacturer’s or institutional normal databases [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that LVEF and left ventricular volumes are important prognostic factors in patients with CAD and left ventricular dysfunction. There is a strong correlation between gated MPI and reference standard measurements of quantitative LVEF, all of which are relatively independent of the isotope, protocol, standard, and algorithm used (14). In a similar manner, TID measured by all the algorithms notwithstanding with effort type is a specific indicator of severe and extensive coronary disease, and TID with positive MPS is accepted as a predictor of poor clinical outcome (15,16).…”
Section: Discussionmentioning
confidence: 99%